Prospettive Anticlericali Durante Il Fascismo: Chiesa E Stato Nella Rivista «Vita Nova»(1925-1933) - Francisci, Giulio (Rivista di storia del cristianesimo, 2019)
The essay focuses on «Vita nova», which was the Fascist University of Bologna's official journal from 1925 to 1933. Analysing the editorial policy, particularly marked by the hostility towards any increase of Catholic cultural and political influence on the Italian society, the article emphasizes the editorial board's struggle to steer Fascist policy in the cultural and religious domain. So it would like to offer a contribution to the history of Italian anticlericalism. In this perspective the text draws attention to the many journal's articles on the relationship between the Italian State and the Holy See and, more generally, between State and Church, focusing on the essays drafted by the main contributors, such as but not limited to Giuseppe Saitta (the editor and Idealist philosopher as his professor, Giovanni Gentile), Carlo Curcio, Armando Lodolini, Julius Evola and Delio Cantimori. Through the analysis of many archival and published sources the article focuses on some key-moments, like the period prior to the so-called «Conciliation»(1925-1928), the signing of the Lateran Treaties (1929), the following crisis (1931) and the end of the publishing activity (1932-1933).